5(x-3)-4(x-2)=8+3(1/3-x)

Simple and best practice solution for 5(x-3)-4(x-2)=8+3(1/3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)-4(x-2)=8+3(1/3-x) equation:



5(x-3)-4(x-2)=8+3(1/3-x)
We move all terms to the left:
5(x-3)-4(x-2)-(8+3(1/3-x))=0
Domain of the equation: 3-x))!=0
We move all terms containing x to the left, all other terms to the right
-x))!=-3
x!=-3/1
x!=-3
x∈R
We add all the numbers together, and all the variables
5(x-3)-4(x-2)-(8+3(-1x+1/3))=0
We multiply parentheses
5x-4x-(8+3(-1x+1/3))-15+8=0
We multiply all the terms by the denominator
5x*3))-4x*3))-(8+3(-1x+1-15*3))+8*3))=0
We add all the numbers together, and all the variables
5x*3))-4x*3))-(8+3(-1x-44))+8*3))=0
Wy multiply elements
135x^4=0
We do not support expression: x^4

See similar equations:

| 15=-n/2 | | 8x+3/4(8x+4)=3(3x+6)-7 | | 1÷k/1=0÷1 | | 10000*1,08^x=20000 | | 1.1/2m+1=2.1/4 | | -3x-12=-4+x | | X+3=2x-61=180 | | 1/5*k=20 | | 9.2^x-1=2.3^x | | 69a=30 | | 2x+7=13+-2x | | -2(x-3)=x=-3+x-3 | | -41+3x=-41 | | w=235-25 | | -3y-4y+8=8-5y-12 | | 2x+1=5x+2 | | 1/1/2m+1=21/4 | | -5x+3=2x+2-7x | | x+2=-4x+22 | | 11/2m+1=21/4 | | 3/2y+8+90+y+32=180 | | 96-4x=-28 | | 4x+1=5x-7 | | m/3-8=-3 | | x^2=415 | | 2(4w+7)/5=5 | | 2(4w+7/5=5 | | 2x+24+x-24=180 | | x^2*2x^2=150 | | 10x-18=2x+3 | | -1.8=2z-18=5 | | 25x+9x-12=0 |

Equations solver categories